Hypomethylation of long interspersed nuclear element-1 (LINE-1) leads to activation of proto-oncogenes in human colorectal cancer metastasis - Hur, Keun (2013)
OBJECTIVE: Hypomethylation of LINE-1 elements has emerged as a distinguishing feature in human cancers. Limited evidence indicates that some LINE-1 elements encode an additional internal antisense promoter, and increased hypomethylation of this region may lead to inadvertent activation of evolutionarily methylation-silenced downstream genes. However, the significance of this fundamental epigenetic mechanism in colorectal cancer (CRC) has not been investigated previously. DESIGN: We analysed tissue specimens from 77 CRC patients with matched sets of normal colonic mucosa, primary CRC tissues (PC), and liver metastasis tissues (LM). LINE-1 methylation levels were determined by quantitative bisulfite pyrosequencing. MET, RAB3IP and CHRM3 protein expression was determined by western blotting and IHC. MET proto-oncogene transcription and 5-hydroxymethylcytosine (5-hmc) were evaluated by quantitative real-time-PCR. RESULTS: Global LINE-1 methylation levels in LM were significantly lower compared with the matched PC (PC=66.2% vs LM=63.8%; p<0.001). More importantly, we observed that specific LINE-1 sequences residing within the intronic regions of multiple proto-oncogenes, MET (p<0.001), RAB3IP (p=0.05) and CHRM3 (p=0.01), were significantly hypomethylated in LM tissues compared with corresponding matched PC. Furthermore, reduced methylation of specific LINE-1 elements within the MET gene inversely correlated with induction of MET expression in CRC metastases (R=−0.44; p<0.0001). Finally, increased 5-hmc content was associated with LINE-1 hypomethylation. CONCLUSIONS: Our results provide novel evidence that hypomethylation of specific LINE-1 elements permits inadvertent activation of methylation-silenced MET, RAB3IP and CHRM3 proto-oncogenes in CRC metastasis. Moreover, since 5-hmc content inversely correlated with LINE-1 hypomethylation in neoplastic tissues, our results provide important mechanistic insights into the fundamental processes underlying global DNA hypomethylation in human CRC.